2023
DOI: 10.1111/all.15945
|View full text |Cite
|
Sign up to set email alerts
|

Hot topics in allergen immunotherapy, 2023: Current status and future perspective

Magdalena Zemelka‐Wiacek,
Ioana Agache,
Cezmi A. Akdis
et al.

Abstract: The importance of allergen immunotherapy (AIT) is multifaceted, encompassing both clinical and quality‐of‐life improvements and cost‐effectiveness in the long term. Key mechanisms of allergen tolerance induced by AIT include changes in memory type allergen‐specific T‐ and B‐cell responses towards a regulatory phenotype with decreased Type 2 responses, suppression of allergen‐specific IgE and increased IgG1 and IgG4, decreased mast cell and eosinophil numbers in allergic tissues and increased activation thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 218 publications
0
7
0
3
Order By: Relevance
“…In various studies of conventional immunotherapy, it has been shown that immunotherapy restores the body's immune tolerance to allergens through multiple mechanisms, corrects immune imbalances, downregulates allergen‐specific T and B cell responses and results in decreased IgE production and increased IgG4 production 31 . The latter cannot bind to complements, has limited affinity for Fcγ receptors, and most importantly, it competes with allergen‐specific IgE, thus preventing mast cell and basophil degranulation 31–33 . The hallmark of successful SCIT treatment is demonstrated by an increase in serum‐specific IgE in the beginning, a slow decrease over time, and a decrease in serum‐specific IgE that favors an increase in IgG (especially serum‐specific IgG4) 1,34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In various studies of conventional immunotherapy, it has been shown that immunotherapy restores the body's immune tolerance to allergens through multiple mechanisms, corrects immune imbalances, downregulates allergen‐specific T and B cell responses and results in decreased IgE production and increased IgG4 production 31 . The latter cannot bind to complements, has limited affinity for Fcγ receptors, and most importantly, it competes with allergen‐specific IgE, thus preventing mast cell and basophil degranulation 31–33 . The hallmark of successful SCIT treatment is demonstrated by an increase in serum‐specific IgE in the beginning, a slow decrease over time, and a decrease in serum‐specific IgE that favors an increase in IgG (especially serum‐specific IgG4) 1,34 .…”
Section: Discussionmentioning
confidence: 99%
“… 31 The latter cannot bind to complements, has limited affinity for Fcγ receptors, and most importantly, it competes with allergen‐specific IgE, thus preventing mast cell and basophil degranulation. 31 , 32 , 33 The hallmark of successful SCIT treatment is demonstrated by an increase in serum‐specific IgE in the beginning, a slow decrease over time, and a decrease in serum‐specific IgE that favors an increase in IgG (especially serum‐specific IgG4). 1 , 34 Previous studies have shown that the production of allergen specific IgG4 reaction is considered to be a “protective" factor for AIT.…”
Section: Discussionmentioning
confidence: 99%
“…IgG-blocking antibodies, specifically IgG1 and IgG4, represent other biomarkers. Their levels can escalate up to 100-fold during AIT, but the correlation with clinical outcomes remains ambiguous [34]. More recent studies have linked specific IgA1 (sIgA1) and specific IgA2 (sIgA2) with successful AIT outcomes [33 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…AIT is currently the only treatment with potential longlasting disease-modifying effects for allergic diseases. It consists in the administration of high doses of the causative allergens to induce sustained tolerance after treatment discontinuation, which can be defined as a long-term clinical tolerance upon natural exposure or in vivo challenges [11]. Up to date, AIT is indicated for patients with allergic rhinoconjunctivitis, hymenoptera sensitivity, allergic asthma (only for controlled patients), and some food allergies, especially peanut, cow's milk, and hen's egg allergy [12,189].…”
Section: Allergen-specific Immunotherapymentioning
confidence: 99%